Інформаційні технології в управлінні закладами освіти - Отамась, Інна; Otamas, Inna (Видавництво Львівської політехніки, 2018)
Розглянуто інформаційні технології в управлінні закладами освіти. Проаналізо- вано наявні електронні ресурси в межах виконання Національної програми інформатизації.

The article deals with the legislature foundation of informatization of higher educational institutions in Ukraine. The existing electronic resources in higher educational institutions (in institutions of postgraduate education) within the implementation of the National Informatization Program are analyzed.
Information technologies in the management of educational institutions
Keywords: інформаційні технології; електронні ресурси; міжнародні стандарти; informatization of higher educational institutions; electronic resources; standart; models; 004; 378.37